Training and perception of veterinary doctors, managers, employees and volunteers working in shelters in Shelter Animal in Brazil (Research, Society and Development, 2022)
The objectives of this study were to evaluate a training course for employees working in animal shelters through distance education (DE) and their perceptions about management and protocols in Shelter Medicine (SM). A training course was designed in DE format for people working directly or indirectly in a dog and cat shelter. The evaluation of the course and analysis of the participants' perception about the management and protocols in SM were collected through pre- and post-course questionnaires, and the answers were organized in Excel® for descriptive analysis. McNemar's test was used to compare the answers. The course was attended by 554 people from the five regions of Brazil, 40.2% (223/554) were volunteers and 65.7% were from private shelters (364/554). Most participants were unaware of the existence of the Shelter Medicine, but understood the function of the shelter and that the responsibility for homeless animals belongs to the whole society. Majority of the participants totally agreed with some internal policies of the shelters. When comparing the answers from both questionnaires, there was a significant change in the questions about the functions and role of shelters, the practice of vaccinating animals upon admission, and the performance of post-adoption monitoring and counseling. Most participants found the course relevant and useful. Finally, the course had wide dissemination with national interest by those working in animal shelters, which allowed an advance in the critical development on the subject, contributing to the dissemination throughout the country.